Citric acid: a green cross-linker of biomaterials for biomedical application - Salihu, Rabiu; Abd Razak, Saiful Izwan; Ahmad Zawawi, Nurliyana; Abdul Kadir, Mohammed Rafiq; Ismail, Norjihada Izzah; Mat Nayan, Nadirul Hasraf; Jusoh, Norhana; Mohamad, Mohd Riduan (Elsevier, 2021)
The application of biomaterials in biomedicine currently suffers some drawbacks, such as inflammation and immunological responses due to mismatching and/or limited compatibility. Biomaterials that are cross-linked with citric acid (CA), also called citrate-based biomaterials (CBBs), have exhibited advanced in-vitro and in-vivo material properties that make them suitable for various biomedical applications. Tunable mechanical properties, biocompatibility, and biofunctionality are among other factors that make CBBs interesting in this field. To emphasize the safety and greenness nature of CA, in this review, we have highlighted the history, potential considerations of exploration, and a summarized stage-wise criterion for developing CBBs. We also discuss several points of view about the application of CA and CBBs in many different aspects of biomedicine, such as in tissue engineering, cancer therapy, and wound dressings.